2020
DOI: 10.1038/s41557-020-0472-x
|View full text |Cite
|
Sign up to set email alerts
|

Engineered triply orthogonal pyrrolysyl–tRNA synthetase/tRNA pairs enable the genetic encoding of three distinct non-canonical amino acids

Abstract: Expanding and reprogramming the genetic code of cells for the incorporation of multiple distinct non-canonical amino acids (ncAAs), and the encoded biosynthesis of non-canonical biopolymers, requires the discovery of multiple orthogonal aminoacyltransfer RNA synthetase/tRNA pairs. These pairs must be orthogonal to both the host synthetases and tRNAs and to each other. Pyrrolysyl-tRNA synthetase (PylRS)/ Pyl tRNA pairs are the most widely used system for genetic code expansion. Here we reveal that the sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 50 publications
0
108
0
Order By: Relevance
“…Similarly, another recent study demonstrated that an evolved leucyl aaRS from E. coli is orthogonal to the M. barkeri PylRS in mammalian cells, again allowing the incorporation of two ncAAs [361] . Notably, a recent study has also developed a method for incorporating three ncAAs in E. coli , using engineered triply orthogonal aaRS/tRNA pairs to suppress a nonsense codon and two quadruplet codons [362] . With these advances, the incorporation of more than one ncAA within a single target becomes possible, widely expanding the study of PTM combinations.…”
Section: Synthetic Histonesmentioning
confidence: 96%
“…Similarly, another recent study demonstrated that an evolved leucyl aaRS from E. coli is orthogonal to the M. barkeri PylRS in mammalian cells, again allowing the incorporation of two ncAAs [361] . Notably, a recent study has also developed a method for incorporating three ncAAs in E. coli , using engineered triply orthogonal aaRS/tRNA pairs to suppress a nonsense codon and two quadruplet codons [362] . With these advances, the incorporation of more than one ncAA within a single target becomes possible, widely expanding the study of PTM combinations.…”
Section: Synthetic Histonesmentioning
confidence: 96%
“…197 To date, up to three different ncAAs have been incorporated into a single polypeptide chain using multiple orthogonal aaRS/tRNA pairs. 198 However, there is only one example of multiple ncAAs being used for the synthesis of a dual-functional ADC (Fig. 12A).…”
Section: Non-canonical Amino Acidsmentioning
confidence: 99%
“…More recently, two separate classes of pyrrolysyl-tRNA synthetase (PylRS) with the N-terminal domain missing and their corresponding tRNAs were identified to be mutually orthogonal to each other and to a Methanosarcina mazei PylRS/SpetRNA Pyl pair in E coli. By co-expressing all three pairs and ribo-Q1 with a GFP reporter, three distinct ncAAs were incorporated by recoding the UAG stop codon and two quadruplet codons (Dunkelmann et al, 2020). The use of quadruplet codons would allow protein termination with a triplet stop codon.…”
Section: Protein Visualization Using Fluorescent Moleculesmentioning
confidence: 99%